Consumption Pattern of Information and Communication Technology in Agriculture: A Study of Jaipur District (Indian Journal of Extension Education, 2024)
The study was conducted in Girdharipura and Mehla villages of Jaipur district of Rajasthan. The study analyzes how ICT is used for agricultural information in rural regions and evaluates the information and relationship between various ICT tools and farmers. In this research, we used a sample size of 100 farmers with a random selection of 50 farmers from Mehla village and 50 farmers from Girdharipura village, all between the age group of 20 and 55 from June 2021 to December 2021. ICT holds huge potential in the dissemination of agriculture-related information to rural masses for their capacity building. Thus, ICT is rightly hailed as a potentially useful tool for agricultural reforms. Farmers often engage in numerous forms of media consumption and do not limit themselves to a single one. This study suggests that farmers engage in various media consumption such as electronic media, folk media & print media, and ICT tools for agriculture purposes, and weather information. Mehla village was using more electronic media than Girdharipura.